2000
DOI: 10.1152/ajplung.2000.278.6.l1146
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine cytokine signaling mediates effects of rhinovirus on airway responsiveness

Abstract: The airway responses to allergen exposure in allergic asthma are qualitatively similar to those elicited by specific viral respiratory pathogens, most notably rhinovirus (RV), suggesting that the altered airway responsiveness seen in allergic asthma and that elicited by viral respiratory tract infection may share a common underlying mechanism. To the extent that T helper cell type 2 (Th2) cytokines have been implicated in the pathogenesis of allergic asthma, this study examined the potential role(s) of Th2-typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 35 publications
(74 reference statements)
1
26
0
Order By: Relevance
“…Other studies have shown that cytokine exposure (4,5) and rhinovirus infection (6) give this same physiologic phenotype, which is accompanied by a several-fold increase in ASM G αi expression. It remains unclear how the 2 proasthmatic phenotypes of hyperresponsiveness to bronchoconstriction and resistance to bronchodilatation, which are mediated by G q - and G s -coupled receptors, respectively, could be influenced by the cellular expression levels of G i .…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Other studies have shown that cytokine exposure (4,5) and rhinovirus infection (6) give this same physiologic phenotype, which is accompanied by a several-fold increase in ASM G αi expression. It remains unclear how the 2 proasthmatic phenotypes of hyperresponsiveness to bronchoconstriction and resistance to bronchodilatation, which are mediated by G q - and G s -coupled receptors, respectively, could be influenced by the cellular expression levels of G i .…”
Section: Introductionmentioning
confidence: 78%
“…Figure 1 shows that tracheal expression of G αi2 assessed by Western blot increased approximately 8-fold upon IL-13 induction in these transgenic mice. These data pointed toward increased G i as a common feature of asthmatic-like airways from passive sensitization with asthmatic serum (3), cytokines (4,5), and rhinovirus exposure (6) as well as increased IL-13 production. However, these prior studies do not indicate whether isolated changes in G i levels influence airway contraction or relaxation responses, nor do they implicate the increase in G i in these models as a mechanism that underlies altered airway signaling or address whether the increase represents a compensatory event.…”
Section: G αI2 Is Increased In a Genetic Model Of Asthma And Ptx Altmentioning
confidence: 98%
“…One potential mechanism of the amplification of responses in our coinfection model is IL-1␤-induced upregulation of the receptors responsible for viral infection or detection. Indeed, major-group RVs cause the endogenous release of IL-1␤, which then acts in an autocrine manner to further potentiate inflammatory responses, for example, through upregulation of the RV major group receptor ICAM-1 (18,19,58). However, we found that while IL-1␤ enhanced CXCL8 release from virally infected epithelial cells, it did not augment virally induced ISGs, having no impact on CXCL10 production and in fact modestly reducing CCL5 release, implying that the cooperation of stimuli exerts selective actions on specific pathways.…”
mentioning
confidence: 99%
“…RV infection also induces the hypersecretion of mucus [7], as well as the increased expression and secretion of various cytokines, including interleukin (IL)-1b, IL-6, IL-8, IL-9, IL-11, and tumour necrosis factor-a [6][7][8]. The actions of these cytokines, either individually or in combination, are likely to underlie the clinical manifestation of RV infection [9].…”
mentioning
confidence: 99%